2023
DOI: 10.1101/2023.02.02.526841
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lifelong tissue memory relies on spatially organised dedicated progenitors located distally from the injury

Abstract: It is believed epithelial cells that have participated in a wound repair elicit a more efficient but locally restricted response to future injuries. However here we show that the cell adaptation resulting from a localised tissue damage has a wide spatial impact at a scale not previously noticed. We demonstrate that away from injured site, after a first injury a specific epithelial stem cell population gives rise to long term wound-memory progenitors residing in their own niche of origin. Notably these progenit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…These newly identified wound-distal memory cells display a cell-autonomous transcriptional pre-activated state, enhancing wound repair ability. When the damage has been resolved, and new homeostasis has been re-set, Lrig1 + SCs derived cells remain transcriptionally pre-activated ( 13 ).…”
Section: Inflammatory Memory Of Epdscsmentioning
confidence: 99%
See 4 more Smart Citations
“…These newly identified wound-distal memory cells display a cell-autonomous transcriptional pre-activated state, enhancing wound repair ability. When the damage has been resolved, and new homeostasis has been re-set, Lrig1 + SCs derived cells remain transcriptionally pre-activated ( 13 ).…”
Section: Inflammatory Memory Of Epdscsmentioning
confidence: 99%
“…Multiple studies found that repeat inflammatory stimuli can induce inflammatory memory in EpdSCs, resulting in related gene mutations and keratinocyte abnormal proliferation and differentiation ( 12 , 13 , 87 ). Chickens infected with the Rous sarcoma virus usually develop tumors along the wound site after an injury ( 88 ).…”
Section: Inflammatory Memory Of Epdscsmentioning
confidence: 99%
See 3 more Smart Citations